Yoga as lifestyle of postmodern society in Bintaro Jaya - Malini, Kadek Hema; Yasa, I Wayan Suka; Utama, I Wayan Budi (International Journal of Social Sciences and Humanities, 2018)
Yoga is becoming a cultural trend that evolves into a mass culture. The most people, especially in the big cities, practice yoga. It means that yoga becomes popular even more with the role of mass media. Therefore, making yoga as a lifestyle in postmodern society. The popularity of yoga brings the changes impact for the yoga teachings. Regarding the teachings that were originally sacred into profane cultural products. There is a profane transformation of the yoga practice that demonstrates the ideological indoctrination for the purpose of capitalism in the yoga culture industry. It was intended to meet the needs and social satisfaction. It was marked the compromise to the market through commercial cultural products. Thus, yoga products were easily accepted by the public. This could be seen from the emergence of yoga genres that varied and have undergone modification and massification of interest and increase the interest of the audience. Therefore, becoming expand the market share of yoga practices whose goal was to gain profit. There were also classes of teacher training as the impact of this culture industry. It made yoga practices that were originally a purely cultural product transformed into a commodity to generate profits. Yoga teaching was no longer considered a sacred product of spirituality, however, it could also be exploited for the benefit of the market for profit.